Pengaruh Atraksi Wisata Dan Fasilitas Terhadap Kepuasan Pengunjung Di Taman Mini Indonesia Indah Pasca Revitalisasi - Sahda Salsabila; Theodosia C. Nathalia (Journal of Tourism and Economic, 2023)
The aim of this research is to analyze the influence of tourist attractions and the facilities provided on visiting satisfaction at Taman Mini Indonesia Indah after revitalization. The sampling technique was accidental sampling, where the Google Form link was distributed as a questionnaire to 150 tourists. Determining the score on the questionnaire uses a Likert scale of 1 – 4 to determine the certainty of a negative or positive answer which will be tested for reliability and validity, using the SPSS analysis tool. Based on the results of multiple linear regression tests, tourist attractions have a significant influence on visitor satisfaction at TMII post-revitalization with a large influence obtained of 0.392, and tourist facilities have a significant influence on visitor satisfaction at TMII post-revitalization with a large influence obtained of 0.430. Thus, the conclusions obtained by the two independent variables, namely attractions and facilities, have a joint effect on tourist satisfaction.